Mycotoxin concentrations in rice from three climatic locations in Africa as affected by grain quality, production site, and storage duration - Tang, E.N.; Ndindeng, S.A.; Bigoga, J.; Traoré, K.; Silué, D.; Futakuchi, K. (Wiley, 2019)
Information on the mycotoxin contamination of rice in Africa is limited although the risk of contamination is high. In this study, domestic milled rice processed by actors using suboptimal methods was purchased and total fumonisin (FUM), zearalenone, and aflatoxin concentrations determined at 0, 90, and 180 days after storage. Three different climatic locations, Cotonou (Benin) in the Guinea savanna, Yaoundé (Cameroon) in the Tropical forest, and N'diaye (Senegal) in the Sahel, were selected as storage sites. Subsets of the samples collected from Glazoue (Benin), Ndop (Cameroon), and Dagana (Senegal) were stored in plastic woven bags under room conditions in the respective sites with or without calcium oxide (burnt scallop shell—BSS, 0.1% w/w) treatment. Multivariance analysis showed that FUM concentration was positively influenced by the duration of storage only while zearalenone concentration was negatively influenced by relative humidity and head rice but positively by impurities. Zearalenone concentration was also influenced by sample collection/storage location, processing type, and duration of storage. Aflatoxin concentration was influenced negatively by storage room temperature and head rice but positively by impurities and chalky grains. In addition, aflatoxin concentration was influenced by collection/storage location and processing type. BSS treatment followed by storage for 6 months had no effect on the concentration of the three assessed mycotoxins. Strategies to reduce the risk of mycotoxin contamination in study sites will include the improvement of physical rice quality through better pre‐ and postharvest practices and proper packaging of both treated rice and untreated rice in hermetic systems before marketing and storage.